THE FINANCIAL LEASING IN ALBANIA AND ITS FINANCING COSTS - Korbi, Alban; Lleshaj, Llesh (European Scientific Journal, ESJ, 2015)
The Financial Leasing in the developing countries has faced high rates of development, while in Albania although its developing potentials are high, its growing rate is very low, with inconsiderable figures in comparison to the lending level in the country. Countries like Albania which have nearly 99% of the total businesses, small ones, should offer a favorable environment for stimulating the financial leasing, as a new financing alternative in the country. In this study we aim to evidence the leasing market in Albania, analyzed through the importance that this market has toward the assets level of all the non-banks financial institutions and toward the GDP of the country. If we discuss about the financing sources, the most important element is the assessment of their costs, this is because in this study will be shown the econometric relation between the financial leasing costs and the economic indicators such as: The Consumption Price Index (for the purchase of the transport vehicles), Interest rate spread (lending rate minus deposit rate, %), Gross fixed capital formation, private sector (% of GDP), The Index of the automobiles maintenance and reparation value, The Value Index of the retail trade of oil, etc.